Human Behavior and the Social Environment I - Tyler, Susan; Open Textbook Library (Open Textbook Library, 2020)
That's what we are here to find out - Human Behavior and the Social Environment (HBSE) - How do they connect? How does it shape us? Why do we think and feel the way we do? This will be explored throughout this course by examining human behavior throughout life stage developments and our interactions with the social environment. This course will explore theoretical perspectives in Social Work to help provide a foundation for organizing thoughts about client needs and issues they are seeking supports for. Theories will then be connected to important developmental, social, and cultural issues that present throughout each stage of life to create an overall picture of a client's experience and how we can use this information to have a better understanding of how people we work with are influenced and why. Knowledge of typical development in each stage of life will also inform the Social Worker if any other supports, resources, or services may be needed.
I. The Person in Environment -- II. The Biopsychosocial Dimension -- III. The Sociocultural Dimension -- IV. The Social Change Dimension -- V. Pre-Pregnancy & Prenatal Development -- VI. Development in Infancy & Toddlerhood -- VII. Development in Early Childhood -- VIII. Development in Middle Childhood -- IX. Development in Adolescence -- X. Development in Early Adulthood -- XI. Development in Middle Adulthood -- XII. Development in Late Adulthood
In English.
Description based on print resource
Keywords: Psychology -- Textbooks